Reliability and factorial validity of agility tests for soccer players - Sporis, G.; Jukic, I.; Milanovic, L.; Vucetic, V. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to evaluate the reliability and factorial validity of agility tests used in soccer. One hundred fifty (n = 150), elite, male, junior soccer players, members of the First Junior League Team, volunteered to participate in the study. The slalom test (ST) sprint 4 × 5 m (S4 × 5) and sprint 9-3-6-3-6-9 m with 180° turns (S180°) tests had a greater reliability coefficient (a = 0.992, 0.979, and 0.976), whereas the within-subject variation ranged between 2.9 and 5.6%. The mentioned 6 agility tests resulted in the extraction of 2 significant components. The S4×5 test had the lowest correlation coefficient with the first component (r = 0.38), whereas the correlation coefficients of the other 5 agility tests were higher than 0.63. The T-test (TT) showed statistically significant differences between the defenders and midfielders (p < 0.05) and between the defenders and attackers (p < 0.05). Statistical significant differences were determined between the attackers and defenders in the sprint 9-3-6-3-9 m with backward and forward running (SBF) and p < 0.05. It can be concluded that of the 6 agility tests used in this study, the SBF, TT, and S180° are the most reliable and valid tests for estimating the agility of soccer players. According to the results of the study, the TT proved to be the most appropriate for estimating the agility of defenders, the SBF, and S180° for estimating the agility of midfielders, whereas the S4 × 5 test can be used for estimating the agility of attackers.